#### Answer

$-3x^4y^3$

#### Work Step by Step

$\sqrt[3] {-27x^{12}y^9}=-3x^4y^3$
because,
$(-3x^4y^3)^3=-27x^{12}y^9$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-3x^4y^3$

$\sqrt[3] {-27x^{12}y^9}=-3x^4y^3$
because,
$(-3x^4y^3)^3=-27x^{12}y^9$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.